2021
DOI: 10.1007/s00501-021-01142-x
|View full text |Cite
|
Sign up to set email alerts
|

The Basics of Hydrogen Uptake in Iron and Steel

Abstract: Armco iron and L80 steel (according to API 5CT) were charged under various conditions due to often not knowing the exact amount of hydrogen absorbed during operation and laboratory charging. These two materials were charged in sodium chloride (NaCl), sulfuric acid (H2SO4), both with and without addition of thiourea (CH4N2S), and in H2S (NACE TM0177) at open circuit potential.Additionally, cathodic charging was done in sodium chloride and sulfuric acid, both with thiourea added at a current density of 1 mA/cm2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…As discussed in Section 2.2.1, the permeation of H through a sample consists of complicated physicochemical processes including dissociation of molecular H and adsorption on the sample surface, absorption and diffusion of H toward the oxidation side, and recombination and desorption of H molecules from the sample surface. 274 In international standards, e.g., G148-97(2018) 275 and ISO 17081:2004, 276 one-dimensional diffusion perpendicular to the permeation surface is usually assumed, which is reasonable under the condition that the permeation surface is sufficiently large relative to the thickness. In this case, the permeation rate of H atom towards the oxidation side can simply be expressed by Fick's second law.…”
Section: Experimental Mapping Of Hmentioning
confidence: 99%
“…As discussed in Section 2.2.1, the permeation of H through a sample consists of complicated physicochemical processes including dissociation of molecular H and adsorption on the sample surface, absorption and diffusion of H toward the oxidation side, and recombination and desorption of H molecules from the sample surface. 274 In international standards, e.g., G148-97(2018) 275 and ISO 17081:2004, 276 one-dimensional diffusion perpendicular to the permeation surface is usually assumed, which is reasonable under the condition that the permeation surface is sufficiently large relative to the thickness. In this case, the permeation rate of H atom towards the oxidation side can simply be expressed by Fick's second law.…”
Section: Experimental Mapping Of Hmentioning
confidence: 99%
“…For that purpose, gaseous hydrogen contents of different low alloyed steels with a ferritic or martensitic matrix were measured and collected from literature. [13,19,48,[51][52][53] A summary of the literature data is given in a tabular form in Appendix. All measurements were performed using the TDA method after high-pressure hydrogen charging of samples in closed autoclave systems.…”
Section: Inverse Parameterization Routinementioning
confidence: 99%
“…Figure2. Verification of the parameter settings by comparing the calculated total hydrogen solubility with measured hydrogen contents for different materials:[13,19,[51][52][53] a-c) bar diagrams and d) predicted versus measured diagram.…”
mentioning
confidence: 99%
“…8,10 Using an As(III) species or thiourea as a hydrogen recombination inhibitor to induce hydrogen absorption into copper is the standard procedure for cathodic charging; however, this causes the rate of hydrogen absorption into copper to be unrealistically high. 14 Similarly, Martinsson et al performed continuous electrochemical charging of OFP copper under aggressive conditions, with the hydrogen content in OFP copper increasing from 0.6 to almost 100 wt. ppm after three weeks.…”
mentioning
confidence: 99%
“…Although the low dose rate and negligible H 2 formation within the humid environment prevent a direct comparison, 11 Vickers microhardness measurements indicated that little to no irradiation hardening occurred to the irradiated pipe despite the constant γ and neutron irradiation during the operation of the NRU reactor, and no blistering was observed on the pipe, which would have been indicative of excess hydrogen absorption. 14 Currently, radiation experiments are being performed on copper samples immersed in water, the results of which will be the focus of a future study.…”
mentioning
confidence: 99%